Electronic Commerce Marketing of Agricultural Products in Karang Sari Village - Rahma Karlinda; Fina Fadila (Journal of Intelligent Business and Technology Science (JIBTec), 2021)
Agriculture is a human activity in the utilization of biological resources to be able to produce food and raw materials to be managed. Many farmers sometimes experience losses due to sales that only get a small profit because some farmers do not have access to good information to promote their products. To improve performance and increase sales of agricultural products, we need an e-commerce application that can verify purchase and sales transaction data, so that information system security, threats, safeguards, security service safe guards. In building this application, you can use the SDLC design model.